2015
DOI: 10.1039/c5cy00393h
|View full text |Cite
|
Sign up to set email alerts
|

SnO2-isolated Pt3Sn alloy on reduced graphene oxide: an efficient catalyst for selective hydrogenation of CO in unsaturated aldehydes

Abstract: In this communication, a pyramid shaped alloy-metal oxidegraphene hybrid was synthesized by a facile procedure, in which SnO 2 nanoparticles (NPs) (4.8-5.8 nm) were first coated onto the surface of reduced graphene oxide (rGO), and then very fine Pt 3 Sn NPs (0.6-1.2 nm) were fabricated on the SnO 2 NPs on rGO sheets under microwave irradiation in a few minutes. Characterizations disclosed that the SnO 2 NPs on rGO were more favorable for the dispersion of Pt, and Pt 3 Sn formed mainly on the surface of SnO 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
57
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 59 publications
4
57
0
Order By: Relevance
“…In general, Pd catalysts are in favor of the hydrogenation of the C=C bond to produce HALD, and Pt‐based catalysts facilitate the production of cinnamyl alcohol (COL) through the hydrogenation of the C=O bond . Although the reduction of the C=C group is favored thermodynamically, it is still challenging to enhance the efficiency of Pd catalysts and lessen Pd usage …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, Pd catalysts are in favor of the hydrogenation of the C=C bond to produce HALD, and Pt‐based catalysts facilitate the production of cinnamyl alcohol (COL) through the hydrogenation of the C=O bond . Although the reduction of the C=C group is favored thermodynamically, it is still challenging to enhance the efficiency of Pd catalysts and lessen Pd usage …”
Section: Introductionmentioning
confidence: 99%
“…[4] Cinnamaldehyde (CAL), as typical a,b-unsaturateda ldehyde, can result in various product distributions in its hydrogenationroute (Scheme 1), depending on the active metal,solvent, and promoter.I ng eneral,P dc atalysts are in favor of the hydrogenation of the C=Cb ond to produce HALD, and Ptbased catalysts facilitate the production of cinnamyl alcohol (COL) through the hydrogenation of the C=Obond. [5] Although the reductiono ft he C=Cg roup is favored thermodynamically, [6][7][8][9][10][11] it is still challenging to enhancethe efficiency of Pd catalysts and lessen Pd usage. [12,13] In recent years, metal nitrides have been studied intensely owing to their synergistic effects andP t-like behavior in tradi-tional catalysis and electrocatalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Fundamental studies have shown that CO oxidation occurs at reduced overpotential at Sn and SnO 2 (or its hydrated form) modied Pt 7-10 and at Pt 3 Sn 11-14 compared to Pt electrodes. Similarly, Sn modied Pt surfaces and Pt 3 Sn catalysts have also shown enhanced activity over Pt for methanol, [15][16][17] ethanol 18-21 and butanol 22 oxidation. In each case the nature of the Sn species, SnO 2 or metallic Sn, and the extent of mixing of the Pt and Sn, alloy formation and the resulting Pt : Sn ratio at the surface, may play a role in determining the activities of the electrocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…PtSn bimetallic nanoparticles (NPs) have attracted considerable attention in heterogeneous and electrocatalyst catalyst research, since the addition of Sn species increases the selectivity of hydrogenation and dehydrogenation for certain molecules [1][2][3] and substantially lowers the activation energy for CO oxidation. [4][5][6] The latter is key to more CO-tolerant catalysts for the anodes of reformate fuelled H 2 PEM fuel cells and direct alcohol fuel cells.…”
Section: Introductionmentioning
confidence: 99%
“…The activity and selectivity observed over the Pt/SiO2 catalyst in the coated tube reactor was considerably higher than that of monometallic Pt catalysts such as Pt/SiO2 [31], Pt/Ti [35] in the flow reactor and Pt/Graphite and Pt/C [12,23,53,54] in the batch reactors ( Figure 9). The performance of Pt/SiO2 coatings is comparable with that of bimetallic supported catalysts such as Pt-Co/SBA-15 [19].…”
Section: Hydrogenation Of Cal Over the Pt/sio2 Catalysts In Batch Andmentioning
confidence: 99%